Derivation of target structure for forests of Norway spruce vegetation zone in Slovakia - M. Moravčík (Journal of Forest Science, 2007)
Forests of the Norway spruce altitudinal vegetation zone occur on the upper limit of tree vegetation and they fulfil important ecological and social functions. A great part of these forests are man-made ones with changed age and spatial structure. The basic objective of the care of these forests is improvement or regeneration of their structure so that it will approach the structure of natural and primeval forests. Maximum fulfilment of their basic functions should be ensured in this way. Therefore following the analysis of our own empirical material the target structure of these forests was derived. Outlook target structure was derived so that it would correspond to the state of the most preserved forest ecosystems occurring in the spruce vegetation zone. Achievable target structure was defined for man-made forests with entirely changed structure.